The Impact of Drought on Native Southern California Vegetation: Remote Sensing Analysis Using MODIS‐Derived Time Series. Issue 6 (16th June 2018) - Okin, Gregory S.; Dong, Chunyu; Willis, Katherine S.; Gillespie, Thomas W.; MacDonald, Glen M.
Abstract: Ecosystems in Mediterranean climates are adapted to seasonal drought. Multiannual drought, however, may significantly affect Mediterranean ecosystems and, further, may affect their constituent communities in different ways with differences in responses emerging during severe drought and over the course of long‐term climate change. This study investigates the response to recent prolonged drought of two important Mediterranean‐climate vegetation types: chaparral and coastal sage scrub. Their greenness was monitored from 2000 to 2017 using the Normalized Difference Vegetation Index (NDVI) derived from the Moderate Resolution Imaging Spectroradiometer. A bootstrapped multiple regression of NDVI anomalies against Palmer Drought Severity Index was used to assess the response of vegetation to drought. The results suggest that drought had a greater effect on chaparral‐dominated ecosystems than coastal sage over the entire region. Shallow‐rooted coastal sage scrub displayed higher interannual variability in NDVI than chaparral but had a lower correlation with Palmer Drought Severity Index. This suggests that this vegetation community is generally less responsive to drought on longer timescales than chaparral, which may be more sensitive to soil water depletion in a prolonged drought. Soil texture plays a critical role in affecting the community sensitivity to drought. For chaparral communities, elevation is negatively correlated with drought sensitivity, suggesting the role of temperature‐related water stress on their long‐term response to drought. Future predicted climate change in the form of increased temperature and drought hazards in Southern California will influence the native ecosystems in nonuniform ways. Long‐term trends in soil moisture depletion and temperature may be particularly important in chaparral‐dominated areas. Plain Language Summary: Chaparral and coastal sage scrub are the two most widely distributed shrubland communities along the South Pacific Coast of California. Shallow‐rooted coastal sage scrub has been presumed to be more vulnerable to drought, compared to the deep‐rooted chaparrals. However, the recent prolonged 2012–2016 drought, which has been reported as the worst drought in the last 1, 200 years, suggests otherwise. Satellite data show that chaparral ecosystems have been more affected by drought than the coastal sage, indicating the higher vulnerability of chaparral over the long term. Chaparral plants are generally more dependent on water in deeper soil layers, making them more resistant to short‐term drought (e.g., <1 year) than coastal sage, but this physiological characteristic, at the same time, makes them susceptible to prolonged droughts (e.g., >2 years). Local response of both communities during drought are dependent upon soil texture, with sandier soils that have higher water holding capacity providing a greater buffer against drought impacts. Chaparral sensitivity to drought, in addition, depends upon elevation that, in turn, controls local temperature. Communities in lower, warmer sites displayed greater drought sensitivity compared to higher, cooler sites, implying that future climate warming may further exacerbate the impact of drought on chaparral ecosystems. Key Points: Impacts of the recent prolonged California droughts on two native vegetation types, chaparral and coastal scrub, were investigated A bootstrapped multiple regression suggests drought had a greater long‐term effect on chaparral‐dominated ecosystems than coastal sage Soil texture and elevation play critical roles in affecting the vegetation sensitivity to water stress